Reflections on Operative Groups on tobacco control in the light of Pichon Rivière (Research, Society and Development, 2021)
Introduction: According to the World Health Organization (WHO) smoking is responsible for the death of more than 8 million people a year. The performance of health operative groups has been widely used for the smoking cessation program. Objective: Reflect on the applicability of operative group theories in smoking cessation, from the perspective of Pichon Rivière. Methodology: This is a reflective study, based on Pichonian theory, developed in the discipline “Group Work Methodology”, of the Post-Graduation Stricto Sensu, Faculty of Nursing, Federal University of Minas Gerais. Results e discussion: Two thematic categories were generated that supported the proposed reflection. The applicability of Operational Groups in smoking cessation allows us to observe the importance of defining the roles of the elements of a smoking group, as well as associating the indicators of the group process. In addition, it allowed us to reflect on the importance of the bond between different individuals, facilitating the process of quitting smoking. Conclusion: The Operative Group as a strategy for patients who wish to quit smoking has several benefits, as in a group, each member can understand the fears and anxieties that the other is going through, reflecting and discussing their actions and thoughts.